Pembuatan Biodiesel Dari Sawit Off Grade Menggunakan Zeolit Alam Teraktivasi Sebagai Katalis Pada Tahap Transesterifikasi - Romie Zulfadli; Zuchra Helwani; Syaiful Bahri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesia has big amount of natural zeolite reserve which is spread in Sumatra, Java and Borneo. It can be utilized as catalyst in transesterification step to produce biodiesel from off grade palm fruit. This research aims to produce biodiesel from low quality raw material and determine the effectiveness of the process by looking at the process conditions effect such as temperature, methanol/oil molar ratio and catalyst concentration on the yield of biodiesel. Biodiesel production from off grade palm oil is done with two step reactions, that is esterification and transesterification. The esterification step is done to reduce free fatty acid (FFA) concentration till <2% as condition in transesterification step. Esterification step use H2SO4 as catalyst, whereas modified zeolite with KOH solution use in transesterification step. Both of process are done in three-neck flask, using magnetic stirrer and condenser. FFA concentration from raw material can be reduce from 11,32% to 0,989% in esterification step with 12:1 methanol/oil ratio, 60 oC temperature and 1%-wt catalyst concentration. Biodiesel with highest yield from transesterification step is 95,84% at 60 oC temperature, 8:1 methanol/oil ratio and 7,36% catalyst concentration. The result of research furthermore processed by Response Surface Methodology (RSM) to determine the effect of process condition toward biodiesel yield. Based on P-value analysis, process conditions that have real effect to the response (biodiesel yield) are temperature and catalyst concentration. Keywords : Biodiesel, Esterification, Natural Zeolite, Off Grade Palm Fruit, Response Surface Methodology (RSM), Transesterification.